Pengaruh Kebijakan Dividen, Kepemilikan Manajerial dan Profitabilitas Terhadap Nilai Perusahaan - Iin Alfhadillah; Dirvi Surya Abbas; Samino Hendrianto (International Forum of Researchers and Lecturers, 2023)
. The purpose of this study was to examine the effect of dividend policy, managerial ownership, institutional ownership and profitability on firm value in banking sector companies listed on the IDX. The population in this study includes all banking companies listed on the IDX in 2017-2021, totaling 47 companies. Based on the sampling technique with purposive sampling obtained a sample of 8 companies. The data analysis method in this study uses panel data regression analysis with the Panel Data Regression Model Equation test. The results of this study indicate that the variables of dividend policy, managerial ownership, and profitability have no effect on firm value. While the variable of institutional ownership has an effect on firm value.